Impact of COVID-19 on ASEAN tourism industry. Issue 2 (4th May 2022) - Beh, Loo-See; Lin, Woon Leong
ABSTRACT: This article aims to examine the extent of the COVID-19 on the tourism industry in ASEAN countries. This study utilized a Panel Vector Autoregression approach to examine the possible bi-directional causality that exists between COVID-19 and tourist arrivals. Data from seven ASEAN nations were used wherein accumulated numbers of cases are hypothesized due to variations in the levels of inbound tourism and other socio-economic differences. The findings indicated two-way causality between COVID-19 and tourist arrivals at the 95% significance level. The results revealed that international tourism can seriously be affected by the COVID-19 outbreak.